Islamic Religious Education through Habituation of Religious of Indonesian Muslim Children in Korea, Before and During the Covid-19 Pandemic - Sonezza Ladyanna; Kim Jang Gyem (Edukasia Islamika : Jurnal Pendidikan Islam, 2022)
he Covid-19 pandemic has had a big impact on various fields of life, including terms habituation of religious teachings to Islamic children in minority areas. In this article, we discuss the comparison of the habituation of religious teachings in Muslim children who came from Indonesia and lived in Korea before and during the Covid-19 pandemic. The research was conducted using qualitative methods in the context of studying religious education and society. The research subjects are Indonesian Muslim families in Korea who have school-age children and attend Korean public schools. The object of research is about religious habituation towards religion before and during the Covid-19 pandemic, namely in the 2020-2021 timeframe. The results showed that there was an increase in the quantity and quality of habituation of religious teachings in Muslim children from Indonesia living in Korea. The increase was obtained from a comparison before and when the Covid-19 pandemic took place. This is due to school policies at home, social distancing, and a ban on feeding in schools during the Covid-19 pandemic.